دراسة ميدانية دور المدرسة في تعزيز قيم المواطنة لدى عينة من الطلبة في المجتمع الكويتي - الكندري, يعقوب يوسف; البيلي, سهير حسين (Sciences de l'Homme et de la Société; Vol. 19 (2016): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ, 2016)
تهدف هذه الدراسة إلى الكشف عن دور المدرسة في الكويت في تأصيل ودعم قيم المواطنة لدى طلابها، فتحاول الدراسة التركيز على مدى ما يمتلكه الطلاب من رصيد معلوماتي عند نهاية مرحلة التعليم المدرسي وبداية التحاقهم بالجامعة وذلك لما لأهمية تلك المرحلة في غرس قيم المجتمع، فتركز الدراسة على المعرفة للمعلومات الدستورية والتاريخية لدى الطالب.   Abstract :                   This study examines the role of school in enhancing the values of citizenship among selected students in Kuwait. This study focuses on the students’ historical and constitutional knowledge. It tried to answer the following questions: how many knowledge that these students earned in their school and what is the relationship between citizenship values and the amount of knowledge. Sample of the present study consists of freshman students at Kuwait University.